Pengaruh Pemanfaatan Teknologi Informasi, Pengendalian Internal Dan Sistem Informasi Akuntansi Terhadap Kinerja Keuangan Organisasi Perangkat Daerah (OPD) Kabupaten Sumbawa - Diva Alifia Ikhsanti; Baiq Kisnawati; Rusdi (Akuntabel: Jurnal Ilmiah Akuntansi, 2026)
The purpose of this study is to investigate how the financial performance of local government agencies (OPD) in Sumbawa Regency is affected by the use of information technology, internal control, and accounting information systems. Thus, the dependent variable in this study is financial performance (Y), while the independent factors are accounting information systems (X3), internal control (X2), and the use of information technology (X1). Employees of OPDs in Sumbawa Regency who work in finance or treasury are the study population. This study uses quantitative and associative methods. Purposive sampling and stratified random sampling methods were used to select the sample. 44 members of finance or treasury staff from OPDs in Sumbawa Regency were sampled. Forty-four online surveys were distributed using Google Forms to collect data. SPSS 25 was used to analyse the data using multiple linear regression and traditional assumption tests. The findings indicate that the financial performance of OPDs is not significantly affected by the use of information technology. On the other hand, the financial performance of OPDs is significantly improved by internal control and accounting information systems.